2015
DOI: 10.1038/ncomms7175
|View full text |Cite
|
Sign up to set email alerts
|

ADAM8 as a drug target in pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) has a grim prognosis with less than 5% survivors after 5 years. High expression levels of ADAM8, a metalloprotease-disintegrin, are correlated with poor clinical outcome. We show that ADAM8 expression is associated with increased migration and invasiveness of PDAC cells caused by activation of ERK 1/2 and higher MMP activities. For biological function, ADAM8 requires multimerisation and associates with β1-integrin on the cell surface. A peptidomimetic ADAM8 inhibitor, BK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(119 citation statements)
references
References 59 publications
3
114
1
1
Order By: Relevance
“…4B). ADAM8 and ADAM10 exhibit overlapping substrate spectra, as exemplified by cleavage of CD23 (36), while ADAM8 expression in mouse skin is strongly up-regulated in the absence of ADAM10 (37). We speculated that ADAM8 might likewise compensate for the loss of ADAM10 in myeloid cells, but observed similar sIL-6R serum levels in ADAM8 knock-out mice as compared to wild type animals (Fig.…”
Section: Adam17 Is the Major Sheddase Of Pma-and Lps-induced Il-6r Shmentioning
confidence: 78%
“…4B). ADAM8 and ADAM10 exhibit overlapping substrate spectra, as exemplified by cleavage of CD23 (36), while ADAM8 expression in mouse skin is strongly up-regulated in the absence of ADAM10 (37). We speculated that ADAM8 might likewise compensate for the loss of ADAM10 in myeloid cells, but observed similar sIL-6R serum levels in ADAM8 knock-out mice as compared to wild type animals (Fig.…”
Section: Adam17 Is the Major Sheddase Of Pma-and Lps-induced Il-6r Shmentioning
confidence: 78%
“…In tumor cells, ADAM8 is implicated in interactions with β1-integrin and ADAM8- dependent FAK and ERK1/2 activation. In a mouse model of PDAC, recent studies using an ADAM8 inhibitor have demonstrated a marked reduction in tumor load, infiltration, and metastasis in vivo (148). …”
Section: Adams and Gastrointestinal Cancermentioning
confidence: 99%
“…Based on structural modeling of the disintegrin domain of ADAM8, Schlomann et al 90 synthesized a 6-amino acid cyclic peptide, designated BK-1361 that prevented multimerization and thus activation of the ADAM8. BK-1361 was found to inhibit ADAM8-dependent cell adhesion and block proteolysis of the ADAM8 substrate, CD23.…”
Section: Adam8 As a Target For Cancer Treatmentmentioning
confidence: 99%